DNA cleavage studies of two Malaysian tropical fruit extracts as a preliminary step towards anti-cancer drug development (Nephelium lappaceum & Artocarpus heterophyllus) - Noor Salehah Jefferi (2013)
Over the past 40 years, there has been a vast interest in developing efficient anticancer drug that possess minimal side effects. There were studies on the ability of plant extract to be used for the treatment of cancer through DNA cleavage activity mechanism. Nephelium lappaceum and Artocarpus heterophyllus were believed to have antioxidant agent called flavonoid and phenolics. These agents which are extracted from the rind of Nephelium lappaceum has been reported to have to have antiproliferative effect associated with apoptosis. Besides, these antioxidant components have been extracted from the seed of Artocarpus heterophyllus. Therefore, in the present study DNA cleavage studies of the ethanolic and aqueous extracts of Nephelium lappaceum and Artocarpus heteropyllus fruits have been performed. Different concentrations of fruit extracts ranging from 5 μl- 25 μl were observed for the plasmid DNA cleavage activity using gel electrophoresis. Both fruits extracts showed a dose dependent increase in activity from lower to higher concentration. The results showed that the extracts of Nephelium lappaceum induced more cleavage against E. coli DNA as compared to that of extracts of Artocarpus heterophyllus./ Thus, these fruits have potential to be used against caertain diseases and further research is warranted in order to develop anticancer drugs.